Genetic Variants of Gonadotropins and Their Receptors Could Influence Controlled Ovarian Stimulation: IVF Data from a Prospective Multicenter Study - Alviggi Carlo; Longobardi Salvatore; Papaleo Enrico; Santi Daniele; Alfano Simona; Vanni Valeria Stella; Campitiello Maria Rosaria; De Rosa Pasquale; Strina Ida; Huhtaniemi Ilpo; Pursiheimo Juha-Pekka; D’Hooghe Thomas; et al. (MDPI, 2025)
Background: Specific polymorphisms might influence controlled ovarian stimulation in women undergoing assisted reproductive technologies (ARTs). Data regarding possible interactions of these polymorphisms are still scanty. The aim of this analysis was to evaluate the effect of polymorphisms of gonadotropins and their receptors in women undergoing ART.
Methods: A total of 94 normogonadotropic patients from three public ART units were enrolled. Patients underwent a gonadotropin releasing hormone (GnRH) long down-regulation protocol with a starting dose of 150 IU of recombinant follicular stimulating hormone (FSH) daily. Eight polymorphisms were genotyped.
Results: A total of 94 women (mean age 30.71 ± 2.61) were recruited. Fewer fertilized and mature oocytes were retrieved in homozygous carriers of luteinizing hormone/choriogonadotropin receptor (LHCGR) 291 (T/T) than in heterozygous C/T carriers (p = 0.035 and p = 0.05, respectively). In FSH receptor (FSHR) rs6165 and FSHR rs6166 carriers, the ratio between total gonadotropin consumption and number of oocytes retrieved differed significantly among three genotypes (p = 0.050), and the ratio was lower in homozygous A/A carriers than in homozygous G/G and heterozygous carriers. Women who co-expressed allele G in FSHR-29 rs1394205 and FSHR rs6166 and allele C LHCGR 291 rs12470652 are characterized by an increased ratio between total FSH dosage and number of oocytes collected after ovarian stimulation (risk ratio: 5.44, CI 95%: 3.18-7.71, p < 0.001).
Conclusions: Our study demonstrated that specific polymorphisms affect the response to ovarian stimulation. Despite this finding, more robust studies are required to establish the clinical utility of genotype analysis before ovarian stimulation.